Digital and ICT Literacy in Distance Education - Solmaz, Ebru; Özcan, Seher; Coşkun, Burcu Karabulut (IGI Global, 2023)
Some studies have shown that the definitions of digital and ICT literacies need clarification, as they are sometimes considered the same thing. Digital literacy refers to the ability to use software or operate a digital device, while ICT literacy involves using digital technology, communication tools, and/or networks to access, manage, integrate, evaluate, create, and transmit information in order to function in an information society. The Covid-19 pandemic has made these two concepts even more critical, as all educational activities are now carried out using technological tools. This chapter aims to define digital and ICT literacies and highlight the differences between these two concepts. Additionally, it will discuss the importance and definitions of these literacies in the context of distance education in the 21st century.
Keywords: 4. Education